Gambaran Pengetahuan Remaja Putri Siswa Kelas IX Tentang Dysminorhoe di Mts Al Hikmah 1 Benda Kabupaten Brebes - Endang Susilowati (Jurnal Health Sains, 2021)
Menarche is defined as the first menstruation, which is the discharge of blood fluid from the female genitals in the form of the decay of the lining of the inner wall in the uterus that contains many blood vessels. The purpose of the study was to find out the knowledge picture of class IX student girls about dismenorhoe in MTS Al Hikmah 1 Benda Brebes Regency. The type of research used in this research is a descriptive research method. Based on the results of research on the Knowledge Picture of Adolescent Girls Class IX about Dismenorhoe in MTS Al Hikmah 1 Brebes Regency, this shows that most of the students who are respondents to research on the incidence of dysminorhoe are students aged 14 years (59%), then less than half of 15-year-old students amounted to 28 people (28%),  Then a small percentage of 13-year-old respondents numbered 9 people (9%), and almost none of the respondents were less than 13 years old or over 15 years old. Based on the results of the research that has been outlined, the conclusion that can be drawn is a picture of the knowledge of adolescent girls of class IX MTS Al Hikmah 1 about dysminorhoe based on characteristics, it is known that more than half of the respondents aged 14 years amounted to 59 people and a small percentage of them were aged 12 and 16 years.